Redescription of Lophiodes lugubris (Alcock, 1894), with the largest record of Lophiodes triradiatus (Lloyd, 1909) from the South China Sea (Lophiiformes: Lophiidae) - Ho, Hsuan-Ching; Lin, Chien-Hsiang (Zootaxa, 2022)
A rare lophiid anglerfish species, Lophiodes lugubris, is redescribed on the basis of two syntypes and non-types. It is unique in having only 4 dorsal-fin spines, among the congeners. Examination of specimens reveals this species is widespread in the Indian Ocean and a specimen newly collected from off Dongsha Island represents the first record of the South China Sea, as well as the Pacific Ocean. A largest record specimen of Lophiodes triradiatus known to date is also documented. Comments on the morphology of sagittal otoliths taken from Taiwanese lophiids are provided.